دور الإعلام التربوي في تفعيل عملية التوجيه المدرسي والمهني في الجزائر - عبيدة, صبطي (دفـاتر المـــــــــــخبـر; No 15 (2015): مجلة دفاتر, 2018)
الملخص: يساعد التوجيه المدرسي والمهني التلميذ على اختيار المسار الدراسي والعملي الذي يود متابعته، ويلعب الإعلام التربوي دورا هاما في ذلك.  كما أن له أثر بالغ في بناء اختيارات التلاميذ، ومن ثم الوصول إلى توجيه أقرب إلى الموضوعية، يتلاءم مع قدرات وطموحاتهم، ويعرفهم بحظوظ التخصص في سوق العمل وعليه، جاءت هذه الورقة، لتناول أهمية الإعلام التربوي وما يقدمه من عون في مجال التوجيه المدرسي والمهني للتلاميذ. Abstract :   School and vocational guidance helps students to choose the course of study and work they want to pursue. So the educational media play an important role in this Feld. It also has a great impact on building students' choices, and thus reaching a more objective orientation that matches their abilities and aspirations, and knows the potential of specialization in the labor market. Accordingly, this paper is intended to address the importance of educational media and its assistance in the field of school and vocational guidance for students .